The effects of centella asia tica extract on human periodontal ligament fibroblasts cell line (2630) / Awatef Mohamed Younis - Mohamed Younis, Awatef (2011)
Ceiziella asiatica is a member of a tropical plant family. is known to have medicinal properties such as anti-oxidative stress and anti-inflammation. Since human periodontal ligament fibroblasts (HPLF) play a crucial role in the progression and healing of periodontal tissue inflammation. Therefore enhancing the role of the HPLF would result in promoting and accelerating the healing of periodontal tissues. The present study was designed to assess the effect of different concentrations of aqueous extract of Centella asiatica on the proliferation, cytoprotective activity and alkaline phosphatase activity of human periodontal ligament fibroblast in-vitro. Aqueous extract of Centella asiatica was prepared and concentrations of 2-40 .tg/ml were applied to the human periodontal ligament fibroblasts culture. The viability of human periodontal ligament fibroblast was investigated by MTT cell proliferation assay. The protective effect of Ceiitella asiatica against oxidative stress was done by measuring its effect on the 1-1 202 -induced cell damage. The differentiation of the periodontal ligament fibroblast cell was assessed by alkaline phosphatase (ALP) expression using Fluorescence Microplate Reader. The data were subjected to statistical analysis using ANOVA and Tukey's post hoc test.